Length-optimal tool path planning for freeform surfaces with preferred feed directions based on Poisson formulation. (October 2021) - Zou, Qiang
Abstract: This paper presents an implicit tool path planning method for machining freeform surfaces represented as parametric surfaces or meshes. It is found that generating tool paths with minimum length lies in finding the optimal trade-off between the preferred feed direction field and the constant scallop height. This optimal trade-off can then be achieved by formulating the tool path planning problem as a Poisson problem which minimizes a simple, quadratic energy. Algorithmically, this amounts to solving a well-conditioned sparse linear system, which is computationally convenient and efficient. A series of examples and comparisons have been conducted to validate the method. Highlights: A new linear method to optimize tool path length for freeform surfaces. Scallop heights in between adjacent tool paths can be kept as constant as possible. Machining strip widths along individual tool paths can be maximized.